Answer:
See Explanation
Explanation:
Incomplete question as the function is not given. So, I will give a general solution
Required
Determine the average rate of change from t = 2 to 4
Average rate of change is :
![Rate = (f(b) - f(a))/(b - a)](https://img.qammunity.org/2022/formulas/mathematics/college/owrxn79d3y26675kjet56m427ktjv6w031.png)
In this case: a = 2 and b = 4
So, we have:
![Rate = (f(4) - f(2))/(4 - 2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/aizse3ehhavzitlmmlpf6r2r067vm29zb9.png)
![Rate = (f(4) - f(2))/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/ma5j9eg2l1exl9prkv0b6p4iksdy6vf75q.png)
Assume that the exponential function is:
![f(t) = 3^{-t](https://img.qammunity.org/2022/formulas/mathematics/high-school/una2txvw8wrcvko912jm8rg91zkqq2a5zz.png)
f(4) and f(2) will be:
![\\ f(4) = 3^(-4) = (1)/(81)](https://img.qammunity.org/2022/formulas/mathematics/high-school/24cnhcv31hb4nbqacb7o5f6wq23p1j97x1.png)
![f(2) = 3^(-2) = (1)/(9)](https://img.qammunity.org/2022/formulas/mathematics/high-school/xknn58jkyl3z4fkhosb70yamva34rqy7ms.png)
So:
![Rate = (f(4) - f(2))/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/ma5j9eg2l1exl9prkv0b6p4iksdy6vf75q.png)
![Rate = ((1)/(81) - (1)/(9))/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/2omudfqxhbvzzv5nnp6ivkvr4xqn7wc4qt.png)
Take LCM
![Rate = ((1 - 9)/(81))/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/wg5a9atgosxdvud7z36gdj5egsti262i1w.png)
![Rate = (-(8)/(81))/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/x4rih0e2pzipv08f3otvuyer5sg58sdpx6.png)
![Rate = -(8)/(81)*(1)/(2)](https://img.qammunity.org/2022/formulas/mathematics/high-school/wr4ttirpcw2ip2ab7bdxf2vbzsc5uqqvgf.png)
![Rate = -(4)/(81)](https://img.qammunity.org/2022/formulas/mathematics/high-school/o6fuo0bqpuop4pch7i0yweifihh9sy3xo0.png)
So, the average rate of change is a decrease of 4/81